Perlindungan hukum terhadap investor dalam pasar modal: Perspektif regulasi dan mekanisme penegakan - Ruba’i, Ahmad Ibnu (Maliki Interdisciplinary Journal, 2024)
This article analyses investor protection law in the capital market from the perspective of regulation and enforcement mechanism. The author explains that capital market regulation in Indonesia is governed by Law Number 8 Year 1995 on Capital Market which mandates the establishment of the Financial Services Authority (OJK) as a capital market supervisory and regulatory institution. OJK is tasked with protecting the interests of the public and investors, increasing the growth and stability of the capital market, and encouraging the implementation of the principles of good corporate governance. The author also elaborates that the law enforcement mechanism for investors in the capital market can be done through litigation and non-litigation channels. The author concludes that investor protection law in the capital market is a crucial material to be discussed and developed, considering that the capital market is one of the investment instruments that offers profit opportunities as well as the risk of loss for investors.